STRATEGY PROFILE OF TEACHERS MOVING IN MATHEMATICS LEARNING IN CLASS IV IN PRIMARY SCHOOL - Anjlika Rahayu; yantoro .; Andi Gusmaulia Eka Putri (Jurnal Tunas Pendidikan, 2023)
This research aims to describe the strategy profile of driving teachers in planning, implementing and evaluating mathematics learning in elementary schools. This research was conducted at Jambi City State Elementary School (SD) 1/IV in the even semester of the 2022/2023 academic year. The results of this research indicate that teachers who are active in learning mathematics carry out several steps and learning strategies. The strategy used when planning mathematics learning in class IV is to carry out a diagnostic assessment, understand CP so that it can be reduced to TP and ATP, express each learning activity process in the form of a mathematics teaching module document, prepare teaching tools that support mathematics learning, and manage the environment. class to be conducive to learning mathematics. The learning implementation strategy is to carry out differentiation techniques for mathematical content, processes and products. The strategy profile used by driving teachers in mathematics learning can be used as an example for other teachers in implementing learning that refers to the independent curriculum.